THE IMPACT OF RISING COLORS ON OIL PAINTING BUSINESS - A STUDY: रंगों की बढती कीमतों का तैलचित्र व्यवसाय पर प्रभाव - एक अध्ययन - Jain, Rashmi (International Journal of Research -GRANTHAALAYAH, 2014)
Of all the creatures in the world, only human is such a creature that feels beautiful. Art in human civilization has its origin in the human mind due to curiosity towards beauty. Through this, one feels joyful by expressing his feeling, feeling of the mind, that is, through the expressive art of his beautiful nature. This includes pictures, idol acting, singing, playing and hauttakothat. Its purpose is not only to create but it is also helpful in maintaining the tradition of culture, which is useful for public welfare. Art is usually divided into two categories - Fine art and professional art The main purpose of fine arts is self-drying which gives pleasure to the mind. Second and professional art is an act which helps in fulfilling the needs of society by sustaining one’s livelihood. Commercial art has been a constant contributor. A producer makes his own production keeping this in mind. And serve that production. To make it useful and profitable, it changes in time through rago. Interior designing and painting have taken the form of a major profitable business today. In the interior decoration, the use of Telichitro has reached its fame to the people. In ancient times, the King-Maharaj and the rich man used to use oil in his home on a large scale. The common people used to paint on raw walls with raw colors on the ground, but nowadays, using a good variety of colors in interior designs has opened up new dimensions in this business, which is becoming a means of income and employment of individuals. In this business, using colors to keep the emotions in mind, increase the beauty and variety of the items. संसार के समस्त प्राणियों मे केवल मानव एक ऐसा प्राणी है जो सोन्दर्य की अनुभूति करता है। मानव सभ्यता मे कला की उत्पत्ति मानव मन मे सोन्दर्य के प्रति जिज्ञासा के कारण हुई है। इसके माध्यम से मनुष्य अपने भाव, मन की अनुभूति व्यक्त करके आन्नद महसूस करता है अर्थात उसकी सृतनात्म प्रवृति की अभिव्यक्तिी कला के माध्यम से करता है। इसमें चित्र,मूर्ति अभिनय,गायन,वादन एवं हात्तकोथत शामिल है। इसका उद्देश न केवल सृजन करना है बल्कि यह संस्कृति की परम्परा को बनाये रखने मे भी सहायक होता है, जो जनकल्याण के लिए उपयोगी है। कला को सामान्यतः दो वर्गो मे बाटाॅं जाता है- ललितकला एवं व्यवसायिक कला ललितकला का मुख्य उद्देश्य स्वतः सूखाय होता है जो मन को आन्नद देता है दुसरी और व्यवसायिक कला एक ऐसा कार्य है जिससे किसी की जिविका का निर्वाह होता समाज की आवश्यकताको की पूर्ति करने मे व्यवसायिक कला का निरन्तर योगदान रहा है। एक उत्पादक इसी बात को ध्यान मे रखकर अपना उत्पादन करता है। और उस उत्पादन को सर्व. उपयोगी एवं लाभप्रद बनाने के लिए समय के अनुसार उसमे रगो के माध्यम से परिवर्तन करता है। इन्टिरियर डिजाइनिंग और चित्रकारिता आज एक प्रमुख लाभप्रद व्यवसाय का रूप ले चुकी है। आन्तरिक सज्जा मे तैलचित्रो का अधिक प्रयोग कर इसकी ख्याति को जन जन तक पहुचॅंा दिया है। प्राचीनकाल मे राजा-महाराज एवं धनी व्यक्ति अपनी गृहसज्जा मे तैलचित्रो का प्रयोग बढे पैमाने पर करते थे। आमजनता कच्ची दीवारों पर जमीन पर कच्चे रंगो से चित्रकारी करते थे लेकिन आजकल इन्टिरियर डिजाइनों मे अच्छे किस्म के रंगो का प्रयोग गृहसज्जा मे करके इस व्यवसाय मे नये आयाम खोल दिए है जो व्यक्तियों की आय व रोजगार का साधन बन रहा है। इस व्यवसाय मे भावों को ध्यान मे रखकर रंगो के प्रयोग से वस्तुओं की सुन्दरता और विविधता को बढा देते है।